Perspective on Environmental Influences Causing Nitro-Oxidative Stress and Modulating Neuroendocrine-Immune Function - Müller, Kurt E.; Henz, Diana; Valentine-Thon, Elizabeth (Archives of Clinical and Biomedical Research, 2026)
Since the evolution of single-celled organisms, the development of defense and tolerance mechanisms in relation to other cells, as bacteria and viruses, became a existential goal. Mitochondria were the organizers to reach that target. The increase in atmospheric oxygen facilitated the process. Generating nitro-oxidative stress proved to be an essential step in this direction. Next step consisted in creating the innate immune system to allow identification of the targets of defense reactions. Nuclear-Factor-kB became the activator of pro-inflammatory cytokines. Inflammation is associated with mood disorders. Inducers of this cascade are infections, autoimmune reactions, allergies, as well as toxic, and neurotoxic substances. The question is, can environmental conditions and environmental toxicants likewise stimulate this cascade. The data described here demonstrate that physical and chemical substances in subtoxic levels are, capable of interacting and of triggering such reactions, and also may be a cause for mood-disorders.